Post-mortem MRI in stillbirth: Normal imaging appearances. Issue 148 (March 2022) - Gupta, Neerja; Gupta, Amit; Kumar, Atin; Kabra, Madhulika; Sharma, Raju; Gupta, Arun Kumar; Jana, Manisha
Highlights: Fetal post-mortem MRI can reliably detect most major organ malformations. Variable normal post-mortem changes can mimic pathology. Internal organs show changes in morphology according to gestation age. Maceration changes after fetal demise have confounding imaging correlates. Radiologists should be aware of normal post-mortem findings to avoid misdiagnosis. Abstract: Post-mortem MRI (PMMRI) can reliably detect most major organ malformations in cases of stillbirth. However, variable normal post-mortem changes mimicking pathology make the interpretation difficult. Varying morphological appearances of internal organs could be due to differences in gestational age of the fetuses being evaluated or the presence of maceration changes which occur after fetal demise in-utero. Final differentiation and detection of abnormality require a close interaction and inputs from the geneticist regarding clinical examination of the fetus and thorough evaluation of intranatal imaging records. With the increasing use of PMMRI in cases of fetal demise, it is prudent for the radiologists to be aware of normal post-mortem findings to avoid misdiagnosis.